A new species of Hexamermis Steiner, 1924 (Nematoda, Mermithidae) parasitizing Epilachna paenulata (Germar, 1824) (Coleopera, Coccinellidae) in Argentina - Reboredo, Guillermo R. (2019)
Hexamermis bonaerensis sp. n. a parasite of Epilachna paenulata (Germar, 1824) (Coleoptera, Coccinellidae) from Argentina is described. It is characterized by having the amphids medium sized, rounded oval shaped, the vagina muscularized and slightly protruding with a descending branch forming a loop before joining the uterus. It presents three rows of genital papillae: the ventrolateral in one row with thirteen papillae; the ventral row with two single, three pairs and two single preanal papillae, and with five pairs postanal papillae. Publicación registrada en Zoobank:LSIDurn:lsid:zoobank.org:pub:9F5EA90D-381D-4FC8-8F0F-86B9E1D2F014 Acto nomenclatural:LSIDurn:lsid:zoobank.org:act:35252E81-2E50-4F12-94DF-FC3617971627